ON VALIDATION OF AN EPIDEMIOLOGICAL MODEL - Ayoade, A. A; Ibrahim, M. O; Peter, O. J; Amadiegwu, S (university of eloued -جامعة الوادي, 2019)
An epidemiological model is suitable to study disease dynamics in a population if it possesses the following properties: existence and uniqueness of solution, invariant region, and the positivity of solution. Based on that, we introduce an epidemiological model and the model is examined whether it possesses the aforementioned characteristics or not
article
Keywords: Mathematical Model, Existence and Uniqueness, Invariant Region, Positivity of solution